2019
DOI: 10.1038/s41598-018-37746-6
|View full text |Cite
|
Sign up to set email alerts
|

The methylome of the celiac intestinal epithelium harbours genotype-independent alterations in the HLA region

Abstract: The Human Leucocyte Antigen (HLA) locus and other DNA sequence variants identified in Genome-Wide Association (GWA) studies explain around 50% of the heritability of celiac disease (CD). However, the pathogenesis of CD could be driven by other layers of genomic information independent from sequence variation, such as DNA methylation, and it is possible that allele-specific methylation explains part of the SNP associations. Since the DNA methylation landscape is expected to be different among cell types, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…This locus presents strong linkage disequilibrium and encodes a number of genes related to immune response and immune regulation through self-recognition [49,51], and strongly predisposes to autoimmune diseases such as CeD. In our previous work [34], we claimed to have found a genotype-independent methylation signature in coeliac duodenal epithelia. The finding of a signature in the HLA region common to IBD and CeD reinforces this idea, given that the HLA association with IBD is much weaker (variance explained <5%) than with CeD, and moreover, different HLA haplotypes drive these associations [45].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This locus presents strong linkage disequilibrium and encodes a number of genes related to immune response and immune regulation through self-recognition [49,51], and strongly predisposes to autoimmune diseases such as CeD. In our previous work [34], we claimed to have found a genotype-independent methylation signature in coeliac duodenal epithelia. The finding of a signature in the HLA region common to IBD and CeD reinforces this idea, given that the HLA association with IBD is much weaker (variance explained <5%) than with CeD, and moreover, different HLA haplotypes drive these associations [45].…”
Section: Discussionmentioning
confidence: 98%
“…We therefore chose coeliac disease (CeD), a chronic inflammatory condition of the GI tract with a well-characterized genetic component, to get further insight into methylome specificity. In addition, DNA methylation data for epithelial and immune components of CeD were analysed separately [34]. When we crossed IBD-DMPs with epithelial CeD-DMPs we found that, out of 4205 IBD-DMPs and 43 CeD epithelial-DMPs, 8 were common (representation factor = 17.7, p < 1.5e-08) ( Table 6).…”
Section: Ibd and Epithelial And Immune Cell Fractions Of The Coeliac mentioning
confidence: 99%
“…This locus presents strong linkage disequilibrium and encodes a number of genes related to immune response and immune regulation through self-recognition 37,39 , and strongly predisposes to autoimmune diseases such as CeD. In our previous work 29 , we claimed to have found a genotype-independent methylation signature in celiac duodenal epithelia. The finding of a signature in the HLA region common to IBD and CeD reinforces this idea, given that the HLA association with IBD is much weaker (variance explained <5%) than with CeD, and moreover, different HLA haplotypes drive these associations 33 .…”
Section: Discussionmentioning
confidence: 98%
“…We therefore chose celiac disease (CeD), a chronic inflammatory condition of the GI tract with a well characterized genetic component, to get further insight into methylome specificity. In addition, DNA methylation data for epithelial and immune components of CeD were analyzed separately 29 . When we crossed IBD-DMPs with epithelial CeD-DMPs we found that, out of 4280 IBD-DMPs and 43 CeD epithelial-DMPs, 7 were common (representation factor=17.1, p < 1e-05) ( Table 5).…”
Section: Ibd and Epithelial And Immune Cell Fractions Of The Celiac Dmentioning
confidence: 99%
See 1 more Smart Citation